Pan-cancer analysis of CLDN18.2 shed new insights on the targeted therapy of upper gastrointestinal tract cancers - Wu, Jun; Lu, Jinghua; Chen, Qiuyue; Chen, Haojie; Zheng, Yongqiang; Cheng, Minggang (Frontiers in Pharmacology, 2024)
Background: CLDN18.2 is a widely researched drug target. However, previous research has primarily been based on immunohistochemistry results and focused on gastric cancer.To analyze the potential cancer-targeting effect of CLDN18.2 from a multi-omics perspective, this study quantified CLDN18.2 expression in The Cancer Genome Atlas (TCGA) pan-cancer cohort. Thus, the relationships between CLDN18.2 expression and genomic alterations, immune infiltration, and prognosis were analyzed. Additionally, we performed analyses of the differentially expressed genes and enriched pathways between the high-and low-CLDN18.2 expression groups, as well as the corresponding drug sensitivity analyses.The results indicated that CLDN18.2 was highly expressed in pancreatic adenocarcinoma (PAAD), stomach adenocarcinoma (STAD), colorectal cancer (CRC), and esophageal carcinoma (ESCA). Moreover, the high-and low-CLDN18.2 expression groups presented significant differences in terms of genomic alterations and immune infiltration, such as the levels of methylation and CD4 + T cell infiltration. Furthermore, high CLDN18.2 expression was significantly associated with poor prognosis in bladder urothelial carcinoma (BLCA), ESCA and PAAD. In upper gastrointestinal tract cancers (STAD, ESCA, and PAAD), downregulated gene-enriched pathways were associated with cell signaling, whereas upregulated gene-enriched pathways were associated with angiogenesis. Finally, we identified drugs associated with CLDN18.2 expression to which samples with different levels of expression were differentially sensitive.CLDN18.2 was highly expressed in upper gastrointestinal tract cancers and its expression had a significant effect on genomic alterations and the tumor microenvironment. Additionally, low CLDN18.2 expression was linked to favorable prognosis. Our study reveals the potential value of CLDN18.2 for tumor prognosis and targeted therapy in various cancers, especially upper gastrointestinal tract cancers.